Determinação multirresíduo de agrotóxicos em banana empregando método QuEChERS modificado e UHPLC-MS/MS - Prochnow, Ana Paula Fernandes (2022)
In recent years, it has been possible to observe that the use of pesticides in various cultures has increased alarmingly and, in most cases, is added to an inappropriate practice of use, as well as impr oper disposal. Banana, one of the most produced and consumed fruits in the world, is no exception, making the fruit a target for the presence of these residues. Therefore, the present work aimed to develop a fast and efficient sample preparation method for the determination of pesticide residues in bananas using ultrahigh performance liquid chromatography coupled to serial mass spectrometry (UHPLCMS/MS). Initially, the three variations of the QuEChERS method for extracting/partitioning the analytes were t ested. After choosing the QuEChERS citrate method, several sorbents were tested to clean the extract by extraction in a dispersive solid phase. The Oasis HLB ® sorbent presented the highest efficiency of results, the established amount of the sorbent and ma gnesium sulfate for the cleaning step was chosen through a test of proportion comparison between the two. The proposed method was validated for the determination of 82 pesticides for the banana matrix, which showed recoveries of 70 to 118%, RSD ≤20% and of quantification between 5 and 2 5 µg kg1 . The UHPLCme thod limits MS/MS technique provided high selectivity and sensitivity, and sample preparation using modified QuEChERS is fast and efficient. The method was successfully applied to the analysis of banana samples and four pesticides were found, including pesticides not allowed in Brazil for bananas.